A Scoping Review: Catechin-Rich Gambir as A Potential Functional for the Obesity Management - Meintansari Manik; Setyo Sri Rahardjo; Ratih Puspita Febrinasari (Global Health Science Group, 2023)
Obesity is a complex and severe problem whose prevalence has increased significantly in the last few decades, posing a significant risk to human health. Various weight loss strategies are currently used, and different weight loss supplements are widely available. However, the effectiveness of some of these food supplements is still unknown. Thus, alternative therapy with a pharmaconutrition macronutrient approach is needed. A scoping review is necessary to scope the current article, summarize the scientific data, and guide future investigation into the potential use of catechin-rich gambir for obesity management. Results: Four databases were searched systematically. The scoping review covered articles published after 2013. A total of 251 articles were collected, and five studies (2 experimental studies) met the inclusion criteria. The synthesis results show that catechin-rich gambir has the potential a function in obesity management therapy. This mechanism, through the anti-obesity effect of catechins, is related to the uptake and synthesis of adipose tissue in obese individuals. Conclusions: Available evidence recommends that the catechin content in gambir has the potential for pharmaconutrition therapy for obesity management.